A Sampling Rate Selecting Algorithm for the Arbitrary Waveform Generator - Yindong Xiao; Yu Chen; Ke Liu; Lei Huang; Xing Yang (IEEE Access, 2019)
The arbitrary waveform generator is now commonly used to generate waveforms in many fields. The Nyquist sampling theorem only provides an open interval for the sampling rate selection, but how to determine a specific sampling rate within this open interval has not been discussed. In practice, the sample rate conversion is adopted to convert the arbitrarily selected sample rate to a safe one which keeps the mirror frequency out of a fixed passband of an anti-aliasing filter in an arbitrary waveform generator whose sample rate is variable. To select a safe sample rate with low computational cost and memory requirements for conversion, an algorithm, with fractional sample rate conversion in mind, is proposed in this paper to guarantee the safety of the target sample rate and the bound of resource cost. The experimental results show that not only the computational cost and memory requirements of sampling rate conversion but also the frequency stability and harmonics of the generated signal in the proposed algorithm overcome the method that arbitrary converts the sampling rate to a fixed maximum one.